A functional method of treatment for trophic ulcers of the foot and its stump - Dondoreva, Irina; Boboshko, Ruslan; Zaitsev, Michail; Ponomaryova, Galina; Shevchenko, Yugenyi (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Seventeen patients were examined: 10 with trophic ulcers on the foot, 7 with those on the foot stump. The functional treatment consisted in using weight relieving orthoses on the ankle joint and foot or foot stump by the patients while standing and walking. Drug and topical treatments of trophic ulcers were performed. Resulting from their complex treatment, all the patients (100 %) developed healing of the trophic ulcers. The data of a biomechanical examination showed improvements in weight-bearing capacity of the damaged lower extremity, rhythmicity of walking and stability in statics and dynamics, particularly in patients with foot stumps. Clinical examples of patients with trophic ulcers on the foot and its stump are given. The weight relieving orthosis on the ankle joint and foot is an effective functional method of treatment for trophic ulcers on the plantar surface of the foot or its stump, which promotes healing of the wound without any limitations for the patient’s motor activity. When the trophic ulcer has healed, the patient is provided with an insole and orthopaedic footwear or with a foot prosthesis in case of a stump.